2021
DOI: 10.1155/2021/5531479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Alginate Concentration on Microcapsules Properties Foreseeing the Protection and Controlled Release of Bioactive Substances

Abstract: To understand the abilities of Ca-alginate microcapsules and their specific applications in different fields, it is necessary to determine the physicochemical and structural properties of those formulated microcapsules. In this work, we aimed to study the effect of alginate concentration in the improvement of the encapsulation efficiency (EE) and on the release of phenolic and flavonoid substances. The relationship between the structure of the encapsulated bioactive substance and Ca-alginate network and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…As an amorphous excipient, the SA did not show sharp crystal diffraction peaks. This phenomenon was also observed by Essifi et al [ 32 ]. The naringin diffraction peaks could still be observed in the PM, indicating the crystalline structure of naringin was not changed.…”
Section: Resultssupporting
confidence: 85%
“…As an amorphous excipient, the SA did not show sharp crystal diffraction peaks. This phenomenon was also observed by Essifi et al [ 32 ]. The naringin diffraction peaks could still be observed in the PM, indicating the crystalline structure of naringin was not changed.…”
Section: Resultssupporting
confidence: 85%
“…The percentage of encapsulated phenolic compounds did not depend on the native starch precursor, and the efficiency values ranged from 38 to 45%. Essifi et al 40 described similar results after evaluating the encapsulation of GA in alginate microcapsules using the ionotropic gelation method. However, Goncalves da Rosa et al 11 reported that the encapsulation efficiency of GA in β-cyclodextrin was 80%.…”
Section: Solubility and Swellingmentioning
confidence: 68%
“… where m t / m ∞ is the percentage of the drug released at time t and for all time; k is the description of the macromolecular network system and n is the release exponent indicating the release mechanism. A linear form of the equation can be acquired through plotting ln ( m t / m ∞ ) against ln(t), whose linear coefficient is k and whose angular coefficient is n. The determined n value is used to discover which of the three mechanisms can describe the release behaviour: the n value is less than 0.43; the release follows the Fickian law and the n value is between 0.43 and 0.85; the non-Fickian release mechanism is established, and when the n value is greater than 0.85 it indicates the case II of transport release with a polymer chain relaxation [ 28 ]. Using OriginPro 2018 software, we calculated the squared correlation coefficient (R 2 was used to confirm the accuracy of the model).…”
Section: Methodsmentioning
confidence: 99%